BHLHE22 Expression as a Potential Diagnostic and Prognostic Biomarker in Cervical Cancer - Rachmadina, Rachmadina; Darmawi, Darmawi; Kemal, Rahmat A; Rangkuti, Ina F; Nurkasanah, Siti; Savira, Maya (Scripta Medica, 2025)
Background/Aim: Cervical cancer is a prevalent and deadly form of gynaecological malignancy, particularly among developing countries. BHLHE22 is a transcription factor that functions as a transcriptional inhibitor and is significant in cancer-related regulatory mechanisms. In cervical cancer, epigenetic alterations transpire, notably in the BHLHE22 gene, which influences gene and protein expression. The objective of this research was to examine the protein and gene expression of BHLHE22 in tissue from cervix cancer in comparison to those found in normal cervix, to investigate its association with various clinical profiles and prognoses and to assess the association of BHLHE22 gene expression with tumour-infiltrating immune cells.Methods: This research employed a cross-sectional analytical study and retrospective cohort analyses. The expression of BHLHE22 protein in tissue from cervix cancer and normal cervix was analysed using immunohistochemistry (IHC) examinations. The level of BHLHE22 gene expression, clinical profiles and prognosis were collected from the GTEx and TCGA studies. The association of BHLHE22 expression and tumour-infiltrating immune cells has been investigated using the Pearson correlation test or Spearman’s rank correlation test from the TIMER database.Results: BHLHE22 protein and mRNA expression in cervical cancer decreased considerably compared to the normal cervix, with protein expression reduced by 1.5-fold and mRNA expression reduced by 3.6-fold, respectively. High levels of BHLHE22 expression were determined to be linked with favourable disease-specific survival. Furthermore, BHLHE22 expression positively correlated with tumour-infiltrating immune cells with antitumour immunity.Conclusion: BHLHE22 expression as a biomarker for early detection a prognostic biomarker for disease-specific survival and a modulator of the immune microenvironment in cervical cancer might be suggested.